India-Africa partnership in trade and investment: With focus on the agriculture and food sector - Ashok Gulati; Sandip Das (University of Bonn, Center for Development Research (ZEF), 2020)
India imports more from Africa than Africa does from India. A large share of Indian imports from Africa are oil and minerals. However, the India-Africa relations in food and agriculture are already important but have potentials for expansion. For complex reasons Africa had no transformation of its agriculture comparable to India's during its erstwhile Green Revolution in the 1960s and 70s. The African continent and the Indian Subcontinent still have a lot to learn from each other, especially as food systems and food value chains are modernizing and technologies in agriculture and food sectors are spreading. This paper looks at historical ties between India and Africa. It identifies trade and investment patterns in recent decades and describes the collaborations between India and several African countries in the field of agriculture. Finally, we point at potential areas for mutual cooperation in agriculture of the two regions in the future.
Keywords: Q13; Q17; O19; O55; 330; India; Africa; agriculture; food; economics; trade; investment; innovation; economic cooperation